2008
DOI: 10.4012/dmj.27.573
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH and Addition of Salt on the Adsorption Behavior of Lysozyme on Gold, Silica, and Titania Surfaces Observed by Quartz Crystal Microbalance with Dissipation Monitoring

Abstract: The adsorption behaviors of lysozyme on dentally related Au, SiO2, and TiO2 surfaces were investigated by a quartz crystal microbalance with dissipation monitoring (QCM-D) method. Frequency shifts indicated that while lysozyme (pI 11) was fairly adsorbed on the SiO2 (pI 1.9) surface at both pH 3 and 7, it was adsorbed on TiO2 (pI 6.3) surface only at pH 7. However, adsorption was disturbed by 50 mM NaCl. These results strongly suggested an electrostatic nature of the adsorption behavior. Though a large-scale a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…1a) is surprising in view of earlier studies 4,6,8,9,42,43 which reported that increasing ionic strength is causing a decrease in adsorption of lysozyme on silica surfaces. Tentatively, we attribute the observed insensitivity of the binding characteristics against salt to a compensation of two opposing effects: (a) increasing silanol dissociation due to the added salt; 45,46,49 (b) counter-ions of the salt competing with the protein for the charged surface sites.…”
Section: Protein Bindingmentioning
confidence: 94%
“…1a) is surprising in view of earlier studies 4,6,8,9,42,43 which reported that increasing ionic strength is causing a decrease in adsorption of lysozyme on silica surfaces. Tentatively, we attribute the observed insensitivity of the binding characteristics against salt to a compensation of two opposing effects: (a) increasing silanol dissociation due to the added salt; 45,46,49 (b) counter-ions of the salt competing with the protein for the charged surface sites.…”
Section: Protein Bindingmentioning
confidence: 94%
“…The gold adsorption constant for lysozyme was calculated to be between 0.06 and 0.08 (ref. 44), implying that E100-125 ng of lysozyme are enough to cover the entire surface of the gold support (0.5 cm 2 ). This coverage of the surface leaves still enough protein in solution to control for chaperone activity (the effective concentration of lysozyme in solution would then be E18.5 mM).…”
Section: Methodsmentioning
confidence: 99%
“…The conditions tested were: 1, 5, 10 and 20 mM DnaJ without ATP; 10 mM DnaK in the presence of ATP; 10 mM DnaJ and 0.1 mM DnaK in the presence of ATP; 10 mM DnaJ and 5 mM DnaK in the presence of ATP; 10 mM DnaJ and 10 mM DnaK in the presence of ATP; 10 mM DnaK, 10 mM DnaJ and 20 mM GrpE in the presence of ATP. Refolding experiments at steady state were performed in the presence of 20 mM lysozyme to account for the specificity of the experiments conducted with chaperones and to control for unspecific substratesurface interactions as lysozyme readily adsorbs to gold 43,44 . The gold adsorption constant for lysozyme was calculated to be between 0.06 and 0.08 (ref.…”
Section: Methodsmentioning
confidence: 99%
“…It is suggested that less adsorption of mucin to Ti and SiO2 sensors was mainly due to the electrostatic repulsion because mucin, Ti and SiO 2 were negatively charged. Some researches pointed out that difference of pH value contributed the adhesion of proteins to materials 10,31) . The influence of pH for the adhesion of pellicle proteins to dental materials should be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…When molecules bind to the oscillating quartz crystal, the oscillating frequency decreases in relation to the amount of protein bound to the crystal surface. The amount of protein adsorbed onto the biomaterial can be estimated by the Sauerbrey equation 9) There have been several reports on QCM monitoring for protein adsorption to titanium [10][11][12] . Photocatalytic decomposition of the pellicle on anatase surfaces was also investigated using the QCM method 13) ; however, most QCM studies of protein adsorption were carried out using 5 MHz AT-cut crystals.…”
Section: Introductionmentioning
confidence: 99%